EFL students’ challenges and strategies in practicing to be a news anchor - Hustarna; Dwi Agistiana , Indah; Habizar (Research and Innovation in Language Learning, 2025)
This research aimed to identify the challenges of EFL students faced and to explain the strategies they used to overcome the challenges in practicing to be a news anchor. This research used a descriptive qualitative research method. The data were collected through semi structured interview and analyzed using thematic analysis. The participants were selected using purposive sampling technque, with six students from batch 2023 at one university in Jambi. The findings revealed two main themes . The first theme related to the challenges students faced in practicing to be a news anchor included linguistic challenges (pronunciation of unfamiliar words, limited vocabulary and difficulty maintaining fluency), psychological challenges (nervousness, got blank), fluency and time pressure (adjusting speed to the teleprompter, forgetting the script, mispronouncing some words), and performing appropriate expressions (maintaining facial expressions and intonation). To overcome these challenges, the students used various strategies covering doing practice many times, speaking aloud, watch movies, doing self-regulation (maintaining confidence, avoiding negative thoughts, and using mental and physical approaches), observation and imitation of models (watch real news anchors and videos from several sources), reflective practice through media (using modern and traditional tools), peer support and feedback (peer review and feedback).